2009
DOI: 10.1115/1.2971172
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Syngas From Biomass in Solid Oxide Fuel Cells

Abstract: Conversion of biomass in syngas by means of indirect gasification offers the option to improve the economic situation of any fuel cell system due to lower costs for feedstock and higher power revenues in many European countries. The coupling of an indirect gasification of biomass and residues with highly efficient solid oxide fuel cell (SOFC) systems is therefore a promising technology for reaching economic feasibility of small decentralized combined heat and power production (CHP).The predicted efficiency of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…Ac learc haracteristic absorption peak at around 750 nm was observed for the reduced PMo 12 ,w hich is known as molybdenum blue. When the H n -POM red was discharged using O 2 as the oxidanti nt he fuel cell at room temperature, the maximum power densities for H 3 [16] Thus, the redox potential of the POM used should be in the range of 0.6-1.2 Vt oo xidizet he phenolic structure of lignin and serve as an electron carrieri n the fuel cell. Theoretically,t he standard cell potentiali sl ess than 0.63 Vb ased on the followingc ell reaction [Eq.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ac learc haracteristic absorption peak at around 750 nm was observed for the reduced PMo 12 ,w hich is known as molybdenum blue. When the H n -POM red was discharged using O 2 as the oxidanti nt he fuel cell at room temperature, the maximum power densities for H 3 [16] Thus, the redox potential of the POM used should be in the range of 0.6-1.2 Vt oo xidizet he phenolic structure of lignin and serve as an electron carrieri n the fuel cell. Theoretically,t he standard cell potentiali sl ess than 0.63 Vb ased on the followingc ell reaction [Eq.…”
Section: Resultsmentioning
confidence: 99%
“…However, externalp rocessing is required to convert lignin to suitable fuels. For example, gasification of lignin to syngasi sn ecessary for SOFCs, [3,4] or carbonization to biochar or blending with active carbon prior to fueling DCFCs. [5][6][7] The requirement of external processing to convert lignin to gaseous fuels or biochar not only increases the complexity of the system but also greatlyr educes exergy efficiency.…”
mentioning
confidence: 99%
“…to develop integrated heat pipe interconnector layers (Figure 1), preventing degradation promoting hotspots and performance impeding cold zones. The concept of combining SOC systems and heat pipes has already been successfully tested within the EU-research project BioCellus [13][14][15]. Experimental results showed that internal cooling of stacks could be realized and temperature distributions were equilibrated.…”
Section: Introductionmentioning
confidence: 96%
“…Further stack related problems, in particular fuel leakage and contact loss between electrodes may occur [3]. Thus, the theoretically fast electric load modulation of solid oxide cells is intensely restricted by inertial thermal adaption of cell and stack and the need to prevent fracture of cell components [4,5]. Thermal gradients within the stack structure are to be minimized, notably for cyclic load changing operation conditions.…”
Section: Introductionmentioning
confidence: 99%